Sorg som uttryck för kvinnlig agens i Lukas 7:36-50 och 23:27-31 - Eythorsdottir, Alva (Svensk exegetisk årsbok, 2025)
This paper examines two pericopes in Luke, which I interpret from a feminist point of view, considering the theme of female grief and mourning. I use a narratological method in my close reading but will also consider the historical context of Luke, social and cultural norms regarding grief and mourning, as well as gender roles, during the ancient times and especially the Greco-Roman society, Hellenistic Judaism, and the Hebrew bible. In 7:36-50 I examine the female character, which is referred to as "a sinner", and her act of bathing the feet of Jesus with her tears, drying them with her loose hair, kissing and anointing them with ointment. I also interpret 23:27-31 and the act of the mourning women, whom Jesus refers to as the "Daughters of Jerusalem". In both these cases I find female characters who are grieving their sin as well as mourning the death of Jesus - they express female agency in acts of protest and prophesy. The female "sinner" is trying to change her situation by begging for forgiveness. I will suggest that she is mourning the future death of Jesus as well, by anointing his feet like women used to anoint the dead. The "Daughters of Jerusalem" protest the execution of Jesus. Jesus tells the women to weep for themselves and their children, instead of for him, and thus invites them to join his prophetic mourning over the judgement of the, guilty, Jerusalem. By weeping for themselves, they are also grieving their sin.